Substance use disorders in military veterans: prevalence and treatment challenges - Teeters JB; Lancaster CL; Brown DG; Back SE (Dove Medical Press, 2017)
Jenni B Teeters,1,2 Cynthia L Lancaster,1,2 Delisa G Brown,3 Sudie E Back1,2 1Department of Psychiatry and Behavioral Sciences, Medical University of South Carolina, Charleston, SC, USA; 2Ralph H Johnson Veterans Affairs (VA) Medical Center, Charleston, SC, USA, 3Department of Human Development and Psychoeducation, Howard University, Washington, DC, USA Abstract: Substance use disorders (SUDs) are a significant problem among our nation’s military veterans. In the following overview, we provide information on the prevalence of SUDs among military veterans, clinical characteristics of SUDs, options for screening and evidence-based treatment, as well as relevant treatment challenges. Among psychotherapeutic approaches, behavioral interventions for the management of SUDs typically involve short-term, cognitive-behavioral therapy interventions. These interventions focus on the identification and modification of maladaptive thoughts and behaviors associated with increased craving, use, or relapse to substances. Additionally, client-centered motivational interviewing approaches focus on increasing motivation to engage in treatment and reduce substance use. A variety of pharmacotherapies have received some support in the management of SUDs, primarily to help with the reduction of craving or withdrawal symptoms. Currently approved medications as well as treatment challenges are discussed. Keywords: addiction, alcohol use disorders, drug use disorders, treatment, pharmacotherapy, psychotherapy